2011
DOI: 10.1108/07363761111165949
|View full text |Cite
|
Sign up to set email alerts
|

Healthy brands: establishing brand credibility, commitment and connection among consumers

Abstract: Purpose -With a segment of consumers growing more health conscious, food manufacturers are feeding consumers' desire for more healthy products by "reformulating" their products to create healthier versions as well as positioning complete product lines as "healthier alternatives." The present research aims to examine variables crucial in the brand-building process for brands that are perceived as "healthy." Design/methodology/approach -A conceptual model with a theoretical basis in the branding literature is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 43 publications
2
72
0
6
Order By: Relevance
“…Also he found another study related to the general idea of brand credibility and brand commitment, but used different variables names, for example, study of John et al (2012), they found credibility of leadership had significantly effects on his/her commitment. Another study of Kemp et al (2011), found that brand credibility had positive effect on brand commitment through the mediating variable which is called purchase intention.…”
Section: The Relationship Between Brand Credibility and Brand Commitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Also he found another study related to the general idea of brand credibility and brand commitment, but used different variables names, for example, study of John et al (2012), they found credibility of leadership had significantly effects on his/her commitment. Another study of Kemp et al (2011), found that brand credibility had positive effect on brand commitment through the mediating variable which is called purchase intention.…”
Section: The Relationship Between Brand Credibility and Brand Commitmentmentioning
confidence: 99%
“…Marketing researchers have shown that WOM communication has an impact on consumer attitudes, consumer risk taking, short-term and long-term product judgments and purchase decisions and choice behavior. Kemp (2011) informed that decades of consumer research has shown Word-of-Mouth Communication (WOMC) to be a powerful influence on consumers' brand attitudes, judgments, and purchase intentions. It is generally more influential than advertising due to its higher credibility and more interactive nature.…”
Section: Word Of Mouth Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Em sua maior parte, tais pesquisas tratavam de comprometimento organizacional (Meyer & Allen, 1984;Meyer & Allen,1997;Meyer & Herscovitch 2001;O'Reilly & Chatman 1986, Garbarino & Johnson, 1999Morgan & Hunt, 1994). Diversos estudos, no entanto, já abordaram o comprometimento entre consumidor e marcas (Kemp & Bui, 2011;Fullerton, 2003). Tal comprometimento pode ser traduzido como um desejo duradouro do consumidor em manter um relacionamento com uma marca (Moorman et al, 1992) e seria caracterizado por apegos econômicos, emocionais e psicológicos de consumidores e marcas (Evanschitzky et al, 2006).…”
Section: Introductionunclassified
“…It is important to note that there is a growing segment of health conscious consumers across the world (Kemp & Bui, 2011). In fact, consumer's HC towards the consumption of soft drinks (especially carbonated soft drinks) is increased (Lőrinczi et al, 2009), since carbonated soft drinks consumption has a harmful dietary effect to the human body and it will lead to the risk of obesity, diabetes, cardiovascular disease, and fatty liver disease (e.g., Assy et al, 2008;Davis et al, 2005;Palmer, Boggs, Krishnan, Hu, Singer & Rosenberg, 2008).…”
Section: Health Consciousnessmentioning
confidence: 99%